Postoperative rehabilitation of neurosurgical patients after spinal cord surgery - results of our own study - David Fantalis; Sergey P. Bordovsky; Irina S. Preobrazhenskaya (ZAO "Consilium Medicum", 2022)
Aim. To assess the extent to which cognitive and emotional disorders in patients undergoing spinal cord surgery affect the quality of rehabilitation and, based on the data obtained, to suggest optimization of rehabilitation measures. Materials and methods. The study included 60 patients (30 men and 30 women) whose condition required spinal cord surgery. All patients underwent assessment of somatic and neurological status, as well as quantitative neuropsychological testing. The influence of cognitive and emotional disorders before and after surgery on the severity of pain syndrome and movement disorders was assessed. When included in the study, patients were randomized into the main (30 people) and control (30 people) group. The patients of the main group received cognitive-motor training, which was carried out using the methodological manual Cognitive Training for Patients with Moderate Cognitive Impairment, developed by the staff of the Department of Nervous Diseases and Neurosurgery of the Sechenov First Moscow State Medical University (Sechenov University). Cognitive, emotional, motor disorders, severity of pain syndrome, as well as the quality of life and adherence of patients to cognitive-motor training were assessed 3 and 6 months after the surgical intervention.The severity of cognitive and emotional disorders in patients of the main and control groups did not differ before the operation. Results. After the operation, the severity of cognitive impairments was significantly higher in patients of the control group (p=0.03). Patients in the control group were significantly worse than patients in the main group in performing memory tasks (p=0.00), they also had a significantly lower rate of mental processes (p=0.00). These differences persisted 3 months after surgery (p=0.00). A week after the surgical intervention, the severity of anxiety and depression was significantly higher in patients in the control group (p=0.01). The positive effect of the operation in the form of pain reduction was achieved in all patients, but in the control group there was an increase in the severity of the pain syndrome after six months of observation compared with that after three months. An increase in the severity of the pain syndrome was associated with an increase in depression, anxiety, and cognitive impairment. The analysis showed that patients of the main group with high adherence to cognitive training showed significantly greater positive dynamics both in terms of cognitive functions and in terms of anxiety and depression (p0.05). A survey of patients after inclusion in the study with the provision of prospective recommendations for clinical care showed the following: 58 patients (96.7% of patients) noted that the proposed recommendations for clinical care, from their point of view, would significantly improve their postoperative prognosis. Important points that should be reflected in the clinical guidelines for the management of patients with spinal cord surgery, from the point of view of patients, were: discussion with the doctor of the picture of their illness, duration of hospitalization, expected outcome, prognosis (60 patients, 100%), medical education rehabilitation skills (51 patients, 85% of patients), communicating with patients who have already undergone a similar operation earlier in this surgical department (49 patients, 81.7%), ensuring continuity and discussing the entire rehabilitation route before surgery (60 patients, 100%). Conclusion. Cognitive and emotionally disorders determine the quality of life and rehabilitation of patients who have undergone surgery on the spinal cord. Our results allow us to recommend the inclusion of cognitive-motor training in the rehabilitation program for patients after spinal neurosurgical operations.